Utilizing UAV technology and GIS analysis for ecological restoration: A case study on Robinia pseudoacacia L. in a mine waste dump landscape rehabilitation - George POPESCU; Cosmin Alin POPESCU; Lucian O. DRAGOMIR; Mihai V. HERBEI; Adina HORABLAGA; Alina-Maria ȚENCHE-CONSTANTINESCU; Tudor SĂLĂGEAN; Simion BRUMA; Mihaela DINU-ROMAN (SZABO); Alexandru COLISAR; Vasile CEUCA; Shuraik KADER; et al. (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The rehabilitation of mine waste dumps is a critical environmental challenge, particularly in areas like Uricani, Romania, where such sites are often characterized by hazardous conditions and poor ecological recovery. This study addresses the need for efficient, low-cost solutions for land reclamation by employing UAV photogrammetry and GIS spatial analysis to assess the potential for afforestation with Robinia pseudoacacia L., a species known for its soil stabilization and ecological benefits. Using UAV technology, high-resolution digital terrain models and orthophotos were generated, with an RMSE of 0.086 m, demonstrating the accuracy and efficiency of this method for large-scale landscape initiatives. GIS spatial analysis was performed to create six key terrain maps and four pedoclimatic factor maps, essential for evaluating the site’s suitability for ecological restoration. The pilot afforestation project, which involved planting R. pseudoacacia, achieved a 75% survival rate after four years, suggesting that the species can thrive under the site’s conditions. The landscape design proposal incorporates recreational spaces aimed at benefiting the local community and attracting tourism, thereby contributing to the area’s economic and cultural revitalization. The interdisciplinary integration of UAV surveying, GIS, and landscape design highlights the cost-effectiveness and interdisciplinary nature of this approach, offering a sustainable model for mine waste dump reclamation and future ecological restoration projects.